Türk Otomobil Sektöründen Kurumsal Marka Kişiliğinin Müşteri Memnuniyeti ve Sadakati Üzerine Etkileri - Yazıcı, Hacer Neyir (My University, 2019)
Bacasız sanayi olarak adlandırılan turizm endüstrisinden gelir sağlamak isteyen ülkeler için en önemli hususlardan biri; turist sayısını artırmak ve bu pazardan payelde etmektir. Gün geçtikçe artan bir ivme de seyreden ve alternatif turizm türlerinden olan sağlık turizmi, bazen kişilerin zorunluluğundan; bazen de daha sağlıklı olma isteklerinden ortaya çıkmış olan bir turizm koludur. Sağlık turizmi ve medikal turizm birbirlerinden farklı iki alternatifturizm çeşididir. Sadece tıbbı tedavi amacı güdülen yolculuklar medikal turizm kapsamında incelenirken; spa, termal kaynaklar veya dinlenme amacı ile yapılan diğer turistik faaliyetler genellikle sağlık turizmi içerisinde değerlendirilmektedir.Medikal turizmin yükselen trenddeki arzı birçok ülke tarafından fırsat olarak görülmüştür. Bu talebi karşılamak için gerekli alt yapı, hastaneler, işi gücü, teknolojik donananım ve acente ağları oluşturulmuştur. Asya ülkeleri liderliğinde geliştirilen bu sektör; Ortadoğu ve Güney Amerika coğrafyalarında da rekabet ortamına yol açmaktadır. Türkiye bu rekabet ortamında; özel sektör ve devlet girişimi ile akredite kuruluş, nitelikli başhekim ve personel sayılarında artış sağlamıştır. Bugün Türkiye medikal turizm için en elverişli lokasyonlardan biri haline gelmiştir.Bu çalışmada; alternatif turizm türlerinden medikal turizm üzerinde durulacaktır. Türkiye'nin sahip olduğu potansiyel, sektörel veriler, arz ve alt yapı durumu, SWOT analizi yapılarak yani Türkiye'nin sahip olduğu güçlü ve zayıfyönlerin yanı sıra fırsatlar ve tehditler irdelenecektir.

One of the most important issues for the countries that want to generate ineome from the tourism industry called as smokeless industry is to increase the number of tourists and get share from this market. Health tourism is one of the tourism arms which is one of the alternative tourism types and has an inereasing acceleration day by day, and which is emerged sometimes due to the necessity of individuals and sometimes emerged from the individuals wish to be healthier. Health tourism and medical tourism are two different types oftourism. While travels aiming only for medical treatment are examined within the scope of medical tourism; spa, thermal resources or other touristic activities with the purpose of rest are general\y considered in the health tourism. The supply of medical tourism in rising trend has been seen as an opportunity by many countries. In order to meet this demand, necessary infrastructures, hospitals, work forces, technological equipments and ageney networks were established. Developed under the leadership of Asian countries, this sector also leads to a competitive environment in the Middle East and South America. In this competitive environment, together with the private sector and government initiative Turkey has increased the number of accredited organizations, employees, and qualified head doctors. Today, Turkey has become one of the most convenient locations for the medical tourism.In this study, we will focus on medical tourism which is one of the alternative tourism types. With SWOT analysis,the potential that Turkey has, sectoral data, supply and infrastructure status will be discussed. In other words, with the strengths and weaknesses Turkey has, opportunities and threats to the Turkey will be discussed as well.
Keywords: Medikal Turizm; Medikal Turizmin Gelişimi; Medikal Turizmin SWOT Analizi; Medical Tourism; SWOT Analysis of Medical Tourism; Medical Tourism Development in Turkey; Alternative Tourism